Pengendalian Aphis craccivora Koch. dengan kitosan dan pengaruhnya terhadap penularan Bean common mosaic virus strain Black eye cowpea (BCMV-BlC) pada kacang panjang - Megasari, Dita; Damayanti, Tri Asmira; Santoso, Sugeng (Jurnal Entomologi Indonesia, 2014)
Aphis craccivora is one of the important pests on yard long bean. It causes direct damage and also has an indirect effect as insect vector of the Bean common mosaic virus (BCMV). The research was done to test the effectiveness of chitosan in suppressing aphid population growth, feeding preference and its ability in transmiting BCMV. Chitosan with concentration ranging of 0.1–1.0% were applied on leaves using spraying method at 1 day before BCMV transmission. BCMV was transmitted by using 3 individuals of viruliferous aphids on each plant. Results show that chitosan treatments on leaves or plants significantly suppressed the population and feeding preferences of A. craccivora. Further, treated plants showed lower disease incidence, severity and BCMV titre significantly compared with untreated control plants. The positive effects of chitosan in suppressing population growth as feeding preferences and BCMV transmission might be due to the anti-feedant effect of chitosan on A. craccivora. Based on the result, chitosan at concentration 0.9% is the most effective concentration in suppressing BCMV and its vector A. craccivora.